ρan-ρan - Hogg, Norman (punctum books, 2021)
"With the peristaltic gurglings of this gastēr-investigative procedural - a soooo welcomed addition to the ballooning corpus of slot-versatile bad eggs The Confraternity of Neoflagellants (CoN) - [users] and #influencers everywhere will be belly-joyed to hold hands with neomedieval mutter-matter that literally sticks and branches, available from punctum in both frictionless and grip-gettable boke-shaped formats. A game-changer in Brownian temp-controlled phoneme capture, ρan-ρan's writhing paginations are completely oxygen-soaked, overwriting the flavour profiles of 2013's thN Lng folk 2go with no-holds-barred argumentations on all voice-like and lung-adjacent functions. Rumoured by experts to be dead to the World™, CoN has clearly turned its ear canal arrays towards the jabbering OMFG feedback signals from their scores of naive listeners, scrapping all lenticular exegesis and content profiles to construct taped-together vernacular dwellings housing 'shrooming atmospheric awarenesses and pan-dimensional cross-talkers, making this anticipatory sequel a serious competitor across ambient markets, and a crowded kitchen in its own right. An utterly mondegreen-infested deep end may deter would-be study buddies from taking the plunge, but feet-wetted Dog Heads eager to sniff around for temporal folds and whiff past the stank of hastily proscribed future fogs ought to ©k no further than the roll-upable-rim of ρan-ρan's bleeeeeding premodern lagoon. Arrange yerself cannonball-wise or lead with the #gut and you'll be kersplashing in no times."